تأثير مشاركة لاعبي فلسطين الداخل في دوري المحترفين الفلسطيني لكرة القدم في تماسك الفريق من وجهة نظر الأجهزة الفنية - يوسف، إياد; إرميلي، زياد محمد حسين; كايد، محمود وجيه محمد (الجامعة الأردنية - عمادة البحث العلمي, 2020)
The purpose was to identify the impact of the participation of the players of Palestine in the Palestinian Professional Football League on the cohesion of the team from the point of view of technicians, and determine the relationship of the variables of the level of training certificate and years of experience and age and type of training team cohesion, The researchers used the descriptive approach to suit the nature of the study on a sample composed of (49) members from the technical staff of the Palestinian professional football league (coach، assistant coach، guard trainer) during the 2018/ 2019 sports season. The results of the questionnaire containing 25 items showed that the spirit of unity and familiarity among the members of the team and that professional income players are very high and that the professional players show interest in the results of the other teams in the Palestinian Professional Football League. The results of the questionnaire also showed that the professional players tend to stay away from the responsibility when the results of the team negative، and that the jealousy level between the players and the professional players is high. The study recommends the need to strengthen the spirit of unity and familiarity between the players of one team and work to clarify the roles between the players and coach to reduce the jealousy level amongst the team players.
هدفت هذه الدراسة تعرف إلى تأثير مشاركة لاعبي فلسطين الداخل في دوري المحترفين الفلسطيني لكرة القدم في تماسك الفريق من وجهة نظر الأجهزة الفنية، واستخدم فيها المنهج الوصفي المسحي لملاءمته طبيعتها على عينة تكونت من (49) فنياً من الأفراد العاملين في الأجهزة الفنية في دوري المحترفين الفلسطيني لكرة القدم (المدير الفني، ومساعد المدرب، ومدرب حراس)، خلال الموسم الرياضي 2018/ 2019، كما استخدمت استبانة اشتملت على (25) فقرة، وقد أشارت نتائج الدراسة على أن روح الوحدة والألفة جاءت كبيرة جداً بين أعضاء الفريق، وأن لاعبي الداخل المحترفين يهتمون بنتائج الفرق الأخرى في الدوري الفلسطيني، استبانة وأنهم يميلون إلى التهرب من المسؤولية عندما تسوء نتائج الفريق، كما أظهرت وجود إحساس بالغيرة من اللاعبين غير المحترفين تجاه لاعبي الداخل المحترفين. وتوصي الدراسة بضرورة تعزيز روح الوحدة والألفة بين لاعبي الفريق الواحد، والعمل على توضيح الأدوار بين كل من اللاعبين والمدرب لتجنب وقوع الغيرة بين اللاعبين.
Keywords: الاحتراف الرياضي -- كرة القدم -- التدريب الرياضي -- فلسطين